On the problem of spatial placement of the companies engaged in emotions - Lidin, Konstantin L.; Sumenkova, Maria E. (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
There are whole areas of the modern market in which the emotional aspect of economic behavior initially plays a paramount role. These are the areas of manufacture and distribution of luxury goods, show-business and the so-called the market of cultural values - cinema, theatre, music and so on. The emotions of pleasure, pride and interest are most demanded in the markets. However, not smaller demand exists for the emotions which can be perceived as negative - fear, uneasiness, gloating, anger.The market of emotions is out of control in terms of harm that some emotions can cause to the consumer. The system of protection of consumer rights is not working in this market segment. As a result, “goods filled with emotions” can freely transmit pathogenic (neurotic) images.The main type of enterprises that produce the emotions are the media. The spatial structure of location of such enterprises is poorly investigated. However, it is obvious that most of the emotional contented images are produced in large cities and metropolitan areas - megapolises and megalopolises. The images contain the emotions that are characteristic for the lifestyle of inhabitants living in a large and mega-urban agglomerations.We have developed a special technique of frequency content analysis for measuring the emotional essence of the texts. The method is to measure the relative frequency of lemmas, signifying the emotions of different types and varying intensity. The emotional spectrum of some media outlets in years 2007-2010 were studied. The total input array was of about 250,000 words.